The Function of Common Sense as a Hegemonic Instrument in Paul Beatty's Novel the Sellout - Abadi, Diana Salsabila; Darmawan, Ruly Indra (English Education and Literature Journal (E-Jou), 2025)
This study aims to investigate how deeply ingrained common sense can become as a hegemonic tool of the dominant group, normalizing and naturalizing ideas to the point where they feel like accepted and indisputable realities that can guide actions and thoughts, while also influencing social interactions and identity formation of subaltern groups. This study uses qualitative and descriptive analysis methodologies within the theoretical framework of Antonio Gramsci's theory of hegemony, it is centered on the novel The Sellout by African-American author Paul Beatty that focuses on the interactions and characters in the novel to see how common sense acts as a hegemonic tool that upholds the beliefs, values, and viewpoints of dominant groups. The researcher discovered around forty-two instances of the concept of "common sense" function in the novel The Sellout. However, the total may surpass this figure based on broader interpretations. The researcher picked nine cases that were most pertinent to the research aims of this article. This study found that the novel The Sellout, when analyzed using qualitative and descriptive methods in the context of Antonio Gramsci's approach, successfully captures the function in which common sense acts as a hegemonic tool for upholding the beliefs, values, and viewpoints of dominant groups and, as a result, can influence social dynamics and personal identities